Prevalence of depressive symptoms and knowledge, attitude, and practice among adolescents in Chengdu, China: a cross-sectional study - Jiang, Xinze; Zhao, Qinqin; Zeng, Ruiying; Lei, Nisha; Wang, Liping (Frontiers in Psychiatry, 2025)
ObjectiveAdolescent depression has emerged as a significant public health concern globally, including in China, and grasping a better understanding of adolescents’ views on depression could help design more adapted policies. This study aims to assess the prevalence of depressive symptoms among adolescents and examine their knowledge, attitudes, and practices (KAP) related to depression.MethodsA cross-sectional survey was conducted between September 23, 2024, and December 3, 2024, in primary and middle schools in Shuangliu District, Chengdu. Data were collected through self-administered questionnaires, which included demographic information, assessments of KAP regarding depression, and the Self-Rating Depression Scale (SDS). The possible attitude and practice scores ranged from 9 to 45, interpreted as negative (9-22), moderate (23-31), and positive (32-45).ResultsA total of 541 valid questionnaires were analyzed. Of the respondents, 308 (56.93%) were female, and 109 (20.15%) were from single-parent households. SDS scores indicated that 18 participants (3.33%) exhibited depressive symptoms. The mean knowledge, attitude, practice, and SDS scores were 9.07±5.08 (possible range: 0-18), 33.37±4.28 (possible range: 9-45), 35.77±6.84 (possible range: 9-45), and 37.35±9.07, respectively. Mediation analysis showed that knowledge directly affected attitude (β = 0.128, P=0.019), attitude directly affected practice (β = 0.250, P=0.011), while SDS directly affected both attitude (β = -0.366, P=0.007) and practice (β = -0.637, P=0.008). Meanwhile, SDS has an indirect negative effect on practice (β = -0.090, P=0.005), and knowledge has an indirect positive effect on practice (β = 0.032, P=0.012).ConclusionAdolescents in Chengdu had insufficient knowledge about depression while exhibiting positive attitudes and proactive practices, and most of them were without depressive symptoms. The study identified knowledge items that should be reinforced through educational interventions on adolescent depression. These findings emphasize the need for enhanced mental health education to improve adolescents’ understanding of depression, reinforce positive attitudes, and support proactive mental health practices.